Audiovisual Culture to Prevent Cardiovascular and Metabolic Diseases in Humans - Peña Maldonado, Alma Alicia; Cervantes López, Miriam Janet; González Pérez, Brian; Cruz Casados, Laura Nelly (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Audiovisual culture can be both an obstacle and an ally in the fight against cardiovascular and metabolic diseases, as we move towards an increasingly digitized future, it is crucial to harness the power of the media to foster a culture of prevention and self-care, empowering people to make informed and positive decisions about their health and well-being; Mexicans face a high risk of cardiovascular disease due to a high prevalence of risk factors such as obesity, due to their unhealthy lifestyles